3(7x+1)=9-3(x-4)

Simple and best practice solution for 3(7x+1)=9-3(x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(7x+1)=9-3(x-4) equation:


Simplifying
3(7x + 1) = 9 + -3(x + -4)

Reorder the terms:
3(1 + 7x) = 9 + -3(x + -4)
(1 * 3 + 7x * 3) = 9 + -3(x + -4)
(3 + 21x) = 9 + -3(x + -4)

Reorder the terms:
3 + 21x = 9 + -3(-4 + x)
3 + 21x = 9 + (-4 * -3 + x * -3)
3 + 21x = 9 + (12 + -3x)

Combine like terms: 9 + 12 = 21
3 + 21x = 21 + -3x

Solving
3 + 21x = 21 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
3 + 21x + 3x = 21 + -3x + 3x

Combine like terms: 21x + 3x = 24x
3 + 24x = 21 + -3x + 3x

Combine like terms: -3x + 3x = 0
3 + 24x = 21 + 0
3 + 24x = 21

Add '-3' to each side of the equation.
3 + -3 + 24x = 21 + -3

Combine like terms: 3 + -3 = 0
0 + 24x = 21 + -3
24x = 21 + -3

Combine like terms: 21 + -3 = 18
24x = 18

Divide each side by '24'.
x = 0.75

Simplifying
x = 0.75

See similar equations:

| 2x^2-3=-93 | | 6n^2+17n+7= | | 15x=72 | | 5.3x-2.68=2.12-6.7x | | 1.2x-1.7-2.1x=-1.9x-2.6 | | b^2+5b-50= | | n^2-8n-20= | | 3.5-2x=x+7.5 | | p^2+6p-7= | | 7.6x-3.5x=-65.6 | | 11x+8-4=10x-3 | | k^2-16k+60= | | 8.2x-3.5x=-84.6 | | x-5rx-36=0 | | n^2+17n+72= | | 6x+9=-111 | | 13x+4(3-6x)= | | -7-8x=5(5-8x) | | 9(x-8)+x=10(x-8)+8 | | -4(6x-4)=-36+2x | | 5n^2+42n=-49 | | 3(5s-6)-18=-2(9s+10)-3 | | 49x^2+63x=-20 | | 9+13n-6=8n+17-2n | | -7x+19=-8(4x+7) | | v^2+10v+16= | | -16+x-1=13-16+8 | | -11=-x | | 1-8r=-(3r-1) | | z^2+(3+i)z+3i=0 | | lnx+ln(x+7)=0 | | -18-4x=-6x+14 |

Equations solver categories